A light-responsive, self-immolative linker for controlled drug delivery via peptide- and protein-drug conjugates. Issue 39 (19th August 2019) - Zang, Chuanlong; Wang, Huawei; Li, Tiantian; Zhang, Yingqian; Li, Jiahui; Shang, Mengdi; Du, Juanjuan; Xi, Zhen; Zhou, Chuanzheng
Abstract : Photoirradiation of the PC4AP linker generates an active intermediate that reacts intramolecularly with a primary amine on the carrier peptide/protein, leading to rapid release of the drug without generating any toxic side products. Abstract : When designing prodrugs, choosing an appropriate linker is the key to achieving efficient, controlled drug delivery. Herein, we report the use of a photocaged C4′-oxidized abasic site (PC4AP) as a light-responsive, self-immolative linker. Any amine- or hydroxyl-bearing drug can be loaded onto the linker via a carbamate or carbonate bond, and the linker is then conjugated to a carrier peptide or protein via an alkyl chain. The PC4AP linker is stable under physiologically relevant conditions. However, photodecaging of the linker generates an active intermediate that reacts intramolecularly with a primary amine (the ε-amine of a lysine residue and the N-terminal amine) on the carrier, leading to rapid and efficient release of the drug via an addition–elimination cascade, without generating any toxic side products. We demonstrated that the use of this self-immolative linker to conjugate the anticancer drug doxorubicin to a cell-penetrating peptide or an antibody enabled targeted, controlled delivery of the drug to cells. Our results suggest that the linker can be used with a broad range of carriers, such as cell-penetrating peptides, proteins, antibodies, and amine-functionalized polymers, and thus will find a wide range of practical applications.